Low-velocity impact behaviors of glass fiber-reinforced polymer laminates embedded with shape memory alloy. (15th September 2021) - Wang, Wenzhi; Zhao, Yueran; Chen, Shangjun; Jin, Xiaochao; Fan, Xueling; Lu, Chunsheng; Yang, Chengxing
Abstract: Shape memory alloy wires embedded glass fiber-reinforced polymer (SMA-GFRP) laminates have great potential in engineering applications. In this paper, low-velocity impact behaviors of SMA-GFRP laminates are investigated under different initial impact energies. Firstly, tensile tests are conducted on a single SMA wire and SMA-GFRP laminates to obtain their mechanical parameters. Then, finite element models are established to describe the mechanical behaviors of SMA-GFRP laminates. Finally, experiments and simulations are carried out to explore the low-velocity impact behaviors and damage mechanisms of SMA-GFRP laminates. The results show that, due to their excellent superelastic deformation and shape recovery ability, SMA wires can improve the damage tolerance and impact resistance of GFRP laminates. The damage patterns and mechanisms of SMA-GFRP laminates vary with the increase of initial impact energy. Under low and medium initial impact energies, deformation can be mostly recovered, while under high impact energy, laminates are almost penetrated and deformation cannot be recovered because of breakage of SMA wires. The damage area of laminates increases first and then decreases as the increase of impact energy. The findings provide a guidance for design and evaluation of SMA-GFRP laminates with low-velocity impact resistance.